UPAYA LEMBAGA PENDIDIKAN ISLAM DALAM MENANGKAL RADIKALISME - Heri Cahyono; Arief Rifkiawan Hamzah (Universitas Muhammadiyah Metro, 2018)
This paper aims to reveal and explain the factors of entry and development of radicalism in Islamic educational institutions. Then explain about the anti-radiklalisme Islam education in preventing and tackling radicalism in Islamic educational institutions. Islamic educational institutions in this contemporary era need to get more attention from academics and education practitioners, because Islamic educational institutions are vulnerable to the entry of radical ideas. These ideas are spread by various groups who simultaneously embrace radicalism in Indonesia. On the other hand, Islamic educational institutions are not yet fully prepared and pay attention to the symptoms of radicalism that seek to enter into it. The Islamic educational institution is still focused on its internal, and has not fully responded to the symptoms of radicalism in Indonesia. This paper is focused on Islamic educational institutions, because the concrete form of the implementation of Islamic education is in the institution. Islamic educational institutions have a strong potential to ward off radicalism so as not to freely enter and poison educators and learners. Islamic education institutions in this case need to respond seriously, namely by growing awareness about the existence of radicalism. This awareness will lead to massive movements. Departing from awareness, Islamic education institutions should implement and optimize the management of Islamic education continuously, then apply Islamic education with multicultural, tolerant, and moderate. With this, all educators and learners in educational institutions can have a broad and respectful view, and avoid radicalism.